Code Reviewing in the Trenches: Understanding Challenges, Best Practices and Tool Needs - Greiler, Michaela; Bird, Christian; Storey, Margaret-Anne; MacLeod, Laura; Czerwonka, Jacek (2016)
This technical report is a companion document to the IEEE Software article "Code Reviewing in the Trenches: Understanding Challenges, Best Practices and Tool Needs". It is intended to give a thorough description of our study such that the article in IEEE Software can focus on results and insights that are most relevant to practitioners. In this report, we provide a more in-depth description of the methodology used to conduct our study of code review at Microsoft (see 1. Code Review Study) and share more detailed and comprehensive analyses of the survey results. In the associated appendix below, we also present the survey that we deployed in its entirety, as well as many raw results. The appendix to this technical report can be found here: Appendix